Mutations in NSD1 and NFIX in Three Patients with Clinical Features of Sotos Syndrome and Malan Syndrome - Lu, Yongping; Chong, Pin Fee; Kira, Ryutaro; Seto, Toshiyuki; Ondo, Yumiko; Shimojima, Keiko; Yamamoto, Toshiyuki (Journal of Pediatric Genetics, 2017)
Mutations in nuclear receptor SET domain-containing protein 1 gene (NSD1) are related to Sotos syndrome, which is characterized by overgrowth, macrocephaly, distinctive features, and neurodevelopmental disabilities. On the other hand, mutations in the nuclear factor I/X gene (NFIX) can lead to Malan syndrome, also known as Sotos-like syndrome, or to the Marshall–Smith syndrome. In this study, using next generation sequencing (NGS), we identified de novo mutations in NSD1 and NFIX in three patients with developmental disabilities associated with overgrowth or macrocephaly. Overall, we confirmed that clinical entities of congenital malformation syndromes can be expanded by molecular diagnoses via NGS.
Keywords: next generation sequencing; autistic features; behavioral abnormality